Limited evidence that body size shrinking and shape-shifting alleviate thermoregulatory pressures in a warmer world - Joshua K. R. Tabh; Elin Persson; Maria Correia; Ciarán Ó Cuív; Elisa Thoral; Andreas Nord (Communications Biology)
Abstract Amassing evidence indicates that vertebrates across the globe are shrinking and changing shape concurrent with rising temperatures. Ecogeographical theories assert that these changes should provide thermoregulatory benefits by easing heat dissipation, however, thermophysical models underpinning such theories are highly simplified and lack empirical validation. Using data from three temperature-manipulation experiments, we quantified the contributions of body size and appendage lengths toward thermoregulatory performance in Japanese quail, while simultaneously querying neutral plasticity as an alternative driver of avian shape-shifts. In the cold, body mass and leg length (here, tarsus length) influenced energy costs of warming, but only among juveniles. In the warmth, smaller body sizes, longer legs and longer bills independently reduced energy and water costs of cooling across ages, but whole-body phenotypes necessary to provide even moderate thermoregulatory benefits were rare (2.5%) and required large departures from allometry. Last, rearing in the warmth reduced body sizes and increased appendage lengths comparable to recent changes observed in nature, but emergent morphologies provided no clear thermoregulatory benefit. Our findings question whether shrinking and shape-shifting are indeed easing thermoregulation in birds or reflect selection for such. Neutral plasticity, or relaxed selection against small body size in juveniles, may better explain recent avian shape-shifting.